Resistance mechanisms of tigecycline in Acinetobacter baumannii - Sun, Chunli; Yu, Yunsong; Hua, Xiaoting (Frontiers in Cellular and Infection Microbiology, 2023)
Acinetobacter baumannii is widely distributed in nature and in hospital settings and is a common pathogen causing various infectious diseases. Currently, the drug resistance rate of A. baumannii has been persistently high, showing a worryingly high resistance rate to various antibiotics commonly used in clinical practice, which greatly limits antibiotic treatment options. Tigecycline and polymyxins show rapid and effective bactericidal activity against CRAB, and they are both widely considered to be the last clinical line of defense against multidrug resistant A. baumannii. This review focuses with interest on the mechanisms of tigecycline resistance in A. baumannii. With the explosive increase in the incidence of tigecycline-resistant A. baumannii, controlling and treating such resistance events has been considered a global challenge. Accordingly, there is a need to systematically investigate the mechanisms of tigecycline resistance in A. baumannii. Currently, the resistance mechanism of A. baumannii to tigecycline is complex and not completely clear. This article reviews the proposed resistance mechanisms of A. baumannii to tigecycline, with a view to providing references for the rational clinical application of tigecycline and the development of new candidate antibiotics.